2000
DOI: 10.1111/0022-4537.00154
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness and Interpersonal Communication

Abstract: Many social problems can be traced to interpersonal communication difficulties, just as many proposed interventions to solve social ills also depend on effective interpersonal communication. This article examines three potential relationships between states of mind and social interaction followed by illustrations from research related to five exemplar social issues-developing effective programs for solving workplace communication problems, training the public to detect scams and hoaxes, reducing stereotyping a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
0
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(97 citation statements)
references
References 68 publications
3
91
0
3
Order By: Relevance
“…[25][26][27] In the nonverbal domain of communication, women also tend to be more accurate at perceiving the emotions of others than are men. 28 In the current study, male physicians may have been less proficient at determining actual parent expectations either through direct verbal communication and/or from parents' nonverbal cues and thus were more prone to incorrectly perceiving expectations for antibiotics than were female physicians.…”
Section: Discussionmentioning
confidence: 63%
“…[25][26][27] In the nonverbal domain of communication, women also tend to be more accurate at perceiving the emotions of others than are men. 28 In the current study, male physicians may have been less proficient at determining actual parent expectations either through direct verbal communication and/or from parents' nonverbal cues and thus were more prone to incorrectly perceiving expectations for antibiotics than were female physicians.…”
Section: Discussionmentioning
confidence: 63%
“…Bensing et al (1995) showed that the duration of the general practitioner's gaze was related to the duration of patient speaking time about psycho-social health problems. Moreover, eye contact at appropriate levels has been shown to contribute positively to another's perceptions of an individual's competence and credibility (Heintzman et al 1993, Burgoon 1994). …”
Section: Eyegaze Behaviourmentioning
confidence: 99%
“…Message producers can always bring various aspects of speech-generating in full awareness if they so wish. Burgoon, Burger, and Waldron (2000) have stated that the trick is to know when to bring any attribute under full awareness, how to master that attribute consciously, and when to set it according to values or release it without thinking again.…”
Section: Resultsmentioning
confidence: 99%